1991
DOI: 10.1016/0735-1097(91)90539-l
|View full text |Cite
|
Sign up to set email alerts
|

Atrial septal aneurysm and stroke: A transesophageal echocardiographic study

Abstract: The prevalence and morphologic characteristics of atrial septal aneurysms identified by transesophageal echocardiography in 410 consecutive patients are described. Two groups of patients were compared: Group I consisted of 133 patients referred for evaluation of the potential source of an embolus and Group II consisted of 277 patients referred for other reasons. An atrial septal aneurysm was diagnosed by transesophageal echocardiography in 32 (8%) of the 410 patients. Surface echocardiography identified only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
204
4
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(225 citation statements)
references
References 20 publications
8
204
4
9
Order By: Relevance
“…2 With widespread use of TTE in the 1980s, several studies found its prevalence to be ranging from 0.2% to 1.9%. 3,4 A recent study based on TEE put its prevalence at 4.3% 5 and suggests that it is a more sensitive diagnostic tool than TTE. 5,6 Although 3D TEE clearly showed the aneurysm in this case, 2D TEE is sufficient to make a diagnosis of ASA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 With widespread use of TTE in the 1980s, several studies found its prevalence to be ranging from 0.2% to 1.9%. 3,4 A recent study based on TEE put its prevalence at 4.3% 5 and suggests that it is a more sensitive diagnostic tool than TTE. 5,6 Although 3D TEE clearly showed the aneurysm in this case, 2D TEE is sufficient to make a diagnosis of ASA.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A recent study based on TEE put its prevalence at 4.3% 5 and suggests that it is a more sensitive diagnostic tool than TTE. 5,6 Although 3D TEE clearly showed the aneurysm in this case, 2D TEE is sufficient to make a diagnosis of ASA. Several studies have classified ASA based on morphology and movement of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFO has a prevalence of up to 29% with autopsy studies [3]. PFO is a major cause of cryptogenic stroke; Mas and others have reported that a combination of PFO and ASA imparts an increased risk of stroke [4]. The presence of Staphylococcus, right-sided cardiac vegetation, a lesion greater than 10 mm, and increased mobility of the vegetation were all significant predictors of subsequent embolization [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have linked the presence of ASA to stroke. In 1 study, ASA was significantly more common in patients with stroke than in those without stroke (20 of 133 [15%] versus 12 of 277 [4%]; P <0.05) 12. The combination of a PFO and ASA has been shown to be a significant risk factor for recurrent stroke 10…”
Section: Pfo Definition and Diagnosismentioning
confidence: 99%